INTEGRASI TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Afini, Dewi; Rahayu, Anita; Mutaqin, Mumu Zainal (Dirasa Islamiyya: Journal of Islamic Studies, 2025)
Technological advances in the digital era have influenced nearly every aspect of life, including education. Islamic Religious Education (PAI), as an essential part of the national education system, is also encouraged to adapt to these rapid changes. This study aims to identify the key difficulties PAI teachers face when integrating technology into their teaching, as well as to explore the promising opportunities that can be leveraged to enhance the learning process so that it is more engaging and aligned with the characteristics of today’s students. This research employed a qualitative approach using a literature review and interviews. The literature review was conducted to establish a strong theoretical background, while interviews gathered direct insights from PAI teachers about their practical experiences in implementing technology-based learning. The findings revealed that despite these technical and non-technical barriers, some teachers successfully utilize digital tools, including Google Classroom, WhatsApp, and educational videos, to make learning more interactive, flexible, and relevant. Moreover, with adequate infrastructure, ongoing training, and support, technology integration holds significant potential to improve learning effectiveness and foster the development of religious values in a meaningful and context-based manner.